Beyond the ice limit [compact disc, unabridged] : a Gideon Crew novel - Preston, Douglas J.; Child, Lincoln (Preston, Douglas J. Gideon Crew novel., 2016)
Five years ago, the mysterious and inscrutable head of Effective Engineering Solutions, Eli Glinn, led a mission to recover a gigantic meteorite from a remote island off the coast of South America. The mission ended in disaster when their ship, the Rolvaag, foundered in a vicious storm in the Antarctic waters and broke apart, sinking-along with its unique cargo-to the ocean floor. One hundred and eight crew members perished, and Eli Glinn was left paralyzed. But this was not all. The tragedy revealed something truly terrifying: the meteorite they tried to retrieve was not, in fact, simply a rock. Instead, it was a complex organism from the deep reaches of space.